HOW TO UNDERSTAND DIGITAL PHOTOGRAPHY: A COOPERATIVE AUTOETHNOGRAPHIC STUDY - Kim, Jiyoung; Joo, Hyoungil (AoIR Selected Papers of Internet Research, 2014)
The purpose of this study is to understand the social and cultural implication of the activities of taking ‘selfies’ and the use of Social Network Service (SNS)s through the personal story of a 20s female researcher in Korea. I analyzes my own digital photography activities based on the experience of the use of Cyworld(the first popular social network service in Korea as Facebook) photo albums for three years(2004 2007) and the use of pictures in iPhone album for fifteen months since I use the. The other researcher (40s male) cooperates to answer the questions about how to understand the digital photography activities. We understand the digital photography activities including digital cameras, social network services and smart phones as acts of personal identity configuration and acts of making the personal documentary. As a result, digital photos are used more for archive purpose rather than for document purpose. Also, we found that the digital photography activities can be understood as the interactions between human and non-human actors in the perspective of Actor-Network Theory (ANT).